Geochemical assessment of heavy metal pollution of river basin in Nigeria using stream sediment - Oladipo Awosusi, Oluwafunso; Luqman Adisa, Adeshina (International Journal of Advanced Geosciences, 2020)
Heavy metal pollution has been a source of health problems in humans. These metals are persistent, toxic, non-degradable and often take a long time to be eliminated from the body. This study is, therefore, designed to assess heavy metal pollution of River Basin in Nigeria. Seventy stream sediment samples were systematically collected from an area, approximately 400km2, latitude 7O 00’ and 7O 15’N and longitude 5O 11’ and 5O 19’E. The pollution status of the sediments by heavy metals were assessed by Enrichment Factor (EF), Pollution Load Index (PLI) and Geo-accumulation Index (Igeo). The concentrations of the heavy metals were also compared with United States Environmental Protection Agency (USEPA) Sediment quality guidelines (SQG). The samples were dried in the laboratory, disaggregated, sieved to minus 80 (<177 microns) mesh size using nylon sieve. The sieved samples were, then, digested and the concentrations of As, Co, Fe, Mn, Ni, Pb, V and Zn were determined by Wavelength Dispersive X-ray Fluorescence Spectrometry (WD-XRFS). Results revealed that the mean concentrations of the heavy metals are in the order V>Zn>Pb>As>Ni>Co>Fe>Mn. Furthermore, the mean concentration of lead exceeded both the average world shale and the USEPA SQG values. However, the mean concentration of cobalt, nickel, manganese and zinc were lower than the average world shale values for these elements. The Enrichment Factor (EF) revealed that cobalt was moderately enriched while arsenic and lead were significantly enriched in the sediments. On the basis of the geoaccumulation index, the stream sediments were largely uncontaminated except at some sites that were moderately to strongly contaminated by As and Pb.